PEMANFAATAN ZIPGRADE SEBAGAI MEDIA PENILAIAN UNTUK MEMETAKAN PENGUASAAN SISWA TERHADAP TOPIK PENGUKURAN DI SMK - Mustofa, Zainul (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2020)
The topic of measurement is an important topic that must be mastered by SMK students in the field of computer and network engineering. Teachers as learning facilitators need to map students' mastery in terms of theory and practice as an evaluation material for providing feedback in the form of enrichment and remedial. One of the media that can quickly and accurately map student mastery is ZipGrade. The purpose of this study was to determine students' acquisition of the topic of measurement using ZipGrade. The research method used the case study method. The research subjects were students of computer and network engineering at SMK Al Munawwariyyah in the academic year 2020/2021 by 86 students. The results showed that the average mastery was 47,5%. Some of the concepts that most students find difficult are reading the measured value of the AVO meter, the rule to use AVOmeter, and using the significant figures rules in multiplication and division operations, and predicting the appropriate resistor according to a given value.